Antibiotics, Resistome and Resistance Mechanisms: A Bacterial Perspective - Sultan, Insha; Rahman, Safikur; Jan, Arif Tasleem; Siddiqui, Mohammad Tahir; Mondal, Aftab Hossain; Haq, Qazi Mohd Rizwanul (Frontiers in Microbiology, 2018)
History of mankind is regarded as struggle against infectious diseases. Rather than observing the withering away of bacterial diseases, antibiotic resistance has emerged as a serious global health concern. Medium of antibiotic resistance in bacteria varies greatly and comprises of target protection, target substitution, antibiotic detoxification and block of intracellular antibiotic accumulation. Further aggravation to prevailing situation arose on observing bacteria gradually becoming resistant to different classes of antibiotics through acquisition of resistance genes from same and different genera of bacteria. Attributing bacteria with feature of better adaptability, dispersal of antibiotic resistance genes to minimize effects of antibiotics by various means including horizontal gene transfer (conjugation, transformation, and transduction), Mobile genetic elements (plasmids, transposons, insertion sequences, integrons, and integrative-conjugative elements) and bacterial toxin-antitoxin system led to speedy bloom of antibiotic resistance amongst bacteria. Proficiency of bacteria to obtain resistance genes generated an unpleasant situation; a grave, but a lot unacknowledged, feature of resistance gene transfer.